Determinación de metales pesados en muestras de agua, en el polígono 2 del sector Puyango - Herrera Balcázar, Karely Mabel (2018)
Abstract:In the present research "Determination of heavy metals in water samples in the polygon 2 of the sector Puyango", aims to perform an analysis of the water in the study area, in order to determine if there are concentrations of heavy metals that exceed the permissible limits of the national and international standards for water quality. Water samples were taken at 12 understood different points between the different localities around the Guineo and Chirimoyo creeks. The investigated metals were Barium, Cadmium, Iron, Lead, Vanadium and Zinc. The analyzes perfomed on the water samples were by Atomic Absorption Spectrometry by flame, graphite furnace (AAS) and by Optics Emission Spectroscopy with Inductive Coupling Plasma (ICP-OES). The concentrations of the metals such as Barium, Iron and Zinc are within the established by the standards (NTE INEN 1108, WHO and EPA), while for Cadmium, Lead and Vanadium the concentrations obtained were above the limits permissible standards.